Distribuição espacial e evolução temporal da hanseníase em um município hiperendêmico no estado do Pará - MACEDO, Geraldo Mariano Moraes de (Universidade Federal do Pará, 2017)
Leprosy is a chronic disease which represents a serious public health problem in Brazil. It is manifested by dermatological and neurological signs and symptoms. Considering the hyperendemicity context of leprosy in the state of Pará, it is necessary use tools for designing interventions more effectively in the transmission chain of the disease. The aim of this study was to identify the pattern of spatial distribution and temporal evolution of leprosy in a hyperendemic county in the state of Pará in 2003 to 2013 period, which takes into consideration clinical, demographic and territorial aspects. This is an ecological, collective, observational and retrospective study in the city of Igarapé-Açu, in the state of Pará. Data were collected by means of detection of new cases available in SINAN and local health service files, which were later georeferenced for geostatistical analysis. 226 cases were reported and there is a slight increasing trend of males from 2009; the predominant age is between 15 and 60 years old. The overall detection rate of new cases of leprosy decreased in national, regional, state and municipal levels. With the estimate for 2020, the trend analysis showed that the Igarapé-Açu will surpass the North region. With respect to clinical characteristics, it became clear predominance of dimorphous. The multibacillary pointed a chance to occur approximately 2 times higher in men. The undetermined clinical form was predominant in children under 15 years old. There was a predominance of zero degree of disability, but the degree of disability II was still beyond recommended by the Ministry of Health, having males with a chance of approximately 3 times more likely to evolve with the degree of disability II. There was discharged as cured in most cases, however with a trend in their reduction and an increase in abandonments and transfers. The spatial distribution map of the cases presented a distribution pattern mosaic-like, with several focuses, and multibacillary prevailed throughout the length of the study area. The Kernel analysis revealed "hot areas" of higher concentration of the disease. The influence of multibacillary in the distribution of cases in the micro areas showed a positive spatial correlation with high intensive. It is concluded that the use of geoprocessing techniques in research was important for a better understanding of the epidemiology of leprosy in the region, demonstrating a constant change in the spatial distribution of leprosy in the city, in which areas with highest number of cases were identified, i.e. increased risk of illness; taking into consideration the socio-demographic and clinical factors that have generated important epidemiological and operational indicators for leprosy in the city.